Management of a Dog with Poorly Regulated Diabetes Mellitus, Chronic Pancreatitis, and Suspected Atopy with Cyclosporine - Jörg M. Steiner; Brian J. Huber (Case Reports in Veterinary Medicine)
A 3-year-and-9-months old male neutered Bichon Frise was presented for a second opinion for diabetes mellitus, weight loss, pruritus, and loss of hair. During further work-up, the dog was diagnosed with uncontrolled diabetes mellitus and concurrent diagnoses of pancreatitis and atopy were also suspected. Multiple adjustments of insulin therapy did not improve control of diabetes mellitus. Also, a variety of different treatments failed to improve pruritus. The dog was seen by a veterinary dermatologist who further suspected atopy and started treatment with cyclosporine. Pruritus improved and coincidentally serum Spec cPL and fructosamine concentrations normalized after therapy, suggesting the possibility that cyclosporine may have controlled pancreatic inflammation and improved control of diabetes mellitus. This case report would suggest that further research into autoimmunity in dogs with chronic pancreatitis is warranted. Also, a controlled study is needed and in progress before the use of cyclosporine in dogs with chronic pancreatitis or a subgroup thereof can be advocated.